Seeking The Middle Ground in Precarious Democracy: Interfaith Engagement in Contemporary Indonesian and Turkish Societies Within The Context of Declaration of Human Fraternity - Robby, Hadza Min Fadhli (Journal of Asian Orientation in Theology, 2024)
As the two most populous Muslim nations carrying the status of precarious democracy, Indonesia and Turkey are still trying to be committed to their credentials as nations that hold dear their multireligious community. While Indonesia follows the value of Pancasila to keep interfaith and intercultural solidarity, Turkey still considers the value of secularism as a core concept to equally treat diverse religious and cultural communities of Turkey. Interestingly, while interfaith engagement in the context of Indonesia is much stronger and visible, discussions about interfaith engagements in Turkey have been refrained due to several reasons. This paper will explore the dynamics of interfaith engagements in Indonesia and Turkey, especially between Muslims and Christians (particularly in the case of Catholics) after the Declaration of Human Fraternity between the Vatican and al-Azhar through the theory of interfaith engagement and the theory of democratic citizenship.